2016
DOI: 10.1162/ajhe_a_00060
|View full text |Cite
|
Sign up to set email alerts
|

Recessions, Poverty, and Mortality in the United States: 1993–2012

Abstract: Prior studies suggest that higher unemployment rates reduce mortality, but newer research suggests this relationship may have attenuated in recent decades. Moreover, individual-level evidence shows a negative effect of economic adversity on survival. We revisit this question using county-level data and two additional macroeconomic measures: poverty rates and median incomes. Examining county-level mortality among non-elderly adults from 1993-2012, we find that higher unemployment has modest negative impacts on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Additionally, in many countries, the strict virus containment policies led to sudden and sharp economic disruption, causing massive layoffs. 8 As documented in the previous literature, such economic downturns and high unemployment could also damage population health. 9-15 These factors would increase mortality when strict counter-virus measures were enforced.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, in many countries, the strict virus containment policies led to sudden and sharp economic disruption, causing massive layoffs. 8 As documented in the previous literature, such economic downturns and high unemployment could also damage population health. 9-15 These factors would increase mortality when strict counter-virus measures were enforced.…”
Section: Introductionmentioning
confidence: 85%
“…This could impact the quality of health services and delay medical treatment, which would negatively impact the population health. Additionally, in many countries, the strict virus containment policies led to sudden and sharp economic disruption, causing massive layoffs 8 . As documented in the previous literature, such economic downturns and high unemployment could also damage population healtht [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Disability status by neighborhood proportion was mapped across interpersonal and organizational spheres, reflecting complex interactions within social networks and organizations that are factors in social inclusion. 25 We chose standard economic indicators with known associations with health outcomes, including poverty, 15,16,26 income, 7,27 unemployment, 28,29 education, 4,27,[30][31][32] and health insurance status. 33,34 Educational level and health insurance status are included as service environments in some SDOH conceptual frameworks.…”
Section: Demographic Features Of Socioeconomically Vulnerable Groups mentioning
confidence: 99%
“…However, they did not include other measures such as income per capita or housing prices that capture other aspects of economic conditions. Gordon and Sommers (2016) demonstrated how various economic measures can have different and even opposite effects on health. They found that county-level unemployment rate was associated with small declines in overall mortality consistent with earlier evidence (Ruhm, 2000), but that higher poverty rates and lower median income were associated with larger increases in mortality.…”
Section: Conceptual Frameworkmentioning
confidence: 99%